The role of theology among Christian Indonesians during COVID-19 pandemic – a perspective from Indonesia - ‪Albertus Bagus Laksana (2022)
Natural disasters tend to give rise to a stronger sense of solidarity and togetherness. People would come together in the face of a real, sudden and undeserved suffering of others, partly because natural disasters do not last long. But in a pandemic, things are more uncertain over a prolonged period of time, and theology can play an imperative role in bringing people together to overcome the crisis.